2016
DOI: 10.1021/acs.joc.6b00528
|View full text |Cite
|
Sign up to set email alerts
|

Remote Electronic Effects by Ether Protecting Groups Fine-Tune Glycosyl Donor Reactivity

Abstract: It was established that para-substituted benzyl ether protecting groups affect the reactivity of glycosyl donors of the thioglycoside type with the N-iodosuccinimide/triflic acid promoter system. Having electron donating p-methoxybenzyl ether (PMB) groups increased the reactivity of the donor in comparison to having electron withdrawing p-chloro (PClB) or p-cyanobenzyl ether (PCNB) protecting groups, which decreased the reactivity of the glycosyl donor relative to the parent benzyl ether (Bn) protected glycosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(82 citation statements)
references
References 80 publications
12
70
0
Order By: Relevance
“…Jensen and co-workersr eported the effect of para-substituted benzyl-type protecting groups on the reactivity of thioglycoside glycosyl donors. [15] They found that glycosyl donors that contained electron-donatings ubstituents showed higher reactivities than those that contained electron-withdrawing substituents, whereas the b-selectivity decreased following protection with substituted benzylg roups that contained electron-withdrawing groups.N otably,o ur resultse xhibited the opposite tendency,t hat is, the glycosyl donor that contained NP groups exhibited the highest b-selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Jensen and co-workersr eported the effect of para-substituted benzyl-type protecting groups on the reactivity of thioglycoside glycosyl donors. [15] They found that glycosyl donors that contained electron-donatings ubstituents showed higher reactivities than those that contained electron-withdrawing substituents, whereas the b-selectivity decreased following protection with substituted benzylg roups that contained electron-withdrawing groups.N otably,o ur resultse xhibited the opposite tendency,t hat is, the glycosyl donor that contained NP groups exhibited the highest b-selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that modifying this system might render this type of activation suitable for S N 2-type glycosylation and hence could circumvent those drawbacks (Scheme 2b). Firstly, we proposed to replace the donor benzyl protecting groups with more electron- withdrawing 4-chlorobenzyl groups (PCB), [39] aiming to inductively discourage the formation of oxocarbenium intermediate B . Secondly, we would employ (2-ethynylphenyl)thio group, which differs from Yu’s version by the absence of alkyne terminus substituent, as the latent leaving group to 1) decrease the steric hindrance around the sulfur in the activated donor A , which should discourage the expulsion of the benzothiophene, and 2) ensure a faster gold- catalyzed cyclization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the anomeric effect, highly α‐selective glucosylations are not easy to achieve. Contrary to Fischer glycosylation conditions with simple alcohols like methanol, glycosylation reactions leading to oligosaccharides are often conducted under kinetic control; the kinetic products of glucosylation are typically the equatorial product , . Several methods for selective synthesis of α‐glucosides have been developed over the years.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to Fischer glycosylation conditions with simple alcohols like methanol, glycosylation reactions leading to oligosaccharides are often conducted under kinetic control; the kinetic products of glucosylation are typically the equatorial product. [2,3] Several methods for selective synthesis of α-glucosides have been developed over the years. Among the most famous of these approaches are: i) in-situ anomerization by Lemieux [4] & Gervay-Hague, [5] ii) intermolecular aglycon delivery by Hindsgaul, Stork and Bols, [6] iii) the use of auxiliaries by Boons, Fairbanks and Turnbull, [7] iv) hydrogen bond-mediated aglycon delivery by Demchenko, [8] and v) the Crich α-glucosylation reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation